2009
DOI: 10.1038/nchembio.193
|View full text |Cite
|
Sign up to set email alerts
|

Rapid selection of cyclic peptides that reduce α-synuclein toxicity in yeast and animal models

Abstract: Phage display has demonstrated the utility of cyclic peptides as general protein ligands, but cannot access proteins inside eukaryotic cells. Expanding a novel chemical genetics tool, we describe the first expressed library of head-to-tail cyclic peptides in yeast (Saccharomyces cerevisiae). We applied the library to selections in a yeast model of α-synuclein toxicity that recapitulates much of the cellular pathology of Parkinson’s disease. From a pool of five million transformants, we isolated two related cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 49 publications
1
128
0
Order By: Relevance
“…The Rab proteins are largely ineffectual in protecting HiTox cells on their own ). They do so only when combined with genetic suppressors of different functional classes Kritzer et al, 2009). We found that, unlike the Rab proteins, all four bioactive compounds restored -syn localization to the plasma membrane on their own in HiTox cells (Fig.…”
Section: Chemical Suppressors Of -Syn Toxicity Reverse Mitochondrialmentioning
confidence: 81%
See 2 more Smart Citations
“…The Rab proteins are largely ineffectual in protecting HiTox cells on their own ). They do so only when combined with genetic suppressors of different functional classes Kritzer et al, 2009). We found that, unlike the Rab proteins, all four bioactive compounds restored -syn localization to the plasma membrane on their own in HiTox cells (Fig.…”
Section: Chemical Suppressors Of -Syn Toxicity Reverse Mitochondrialmentioning
confidence: 81%
“…The IntTox strain also can be suppressed by single genetic modifiers (Yeger-Lotem et al, 2009). By contrast, the HiTox -syn strain, which only expresses ~50% more -syn, requires two genetic suppressors acting in separate pathways to rescue growth Kritzer et al, 2009). Transcriptional profiling revealed that, in this strain, in addition to ER-to-Golgi trafficking defects, mitochondrial dysfunction is an early pathological phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, polyphenol-based therapies represent an underexplored strategy to minimize the huge social and economic impact of NDs. The high degree of evolutionary conservation of fundamental biological processes among eukaryotes has established baker's yeast as a validated model organism to decipher the intricacies of human pathologies, particularly NDs, to identify molecular targets amenable to therapeutic intervention as well as lead molecules with health-promoting potential (Kritzer et al 2009;Su et al 2010;Tardiff et al 2012;Menezes et al 2015). BacHBerry aimed at identifying phenolic bioactives from harnessing the diversity of phenolics in selected berry germplasm from cultivated, wild and underutilized species of berries.…”
Section: Berry Extract Bioactivity Screeningmentioning
confidence: 99%
“…11,18,19 The latter uses a selectively randomized library of splitinteins for the production of genetically encoded, backbone cyclized peptide libraries. Semisynthetic libraries are able to incorporate nonpeptidogenic amino acids while retaining ribosomal synthesis and an associated genetic tag.…”
Section: -16mentioning
confidence: 99%